2019
DOI: 10.3348/kjr.2018.0356
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium Deposition in the Brain: Current Updates

Abstract: Gadolinium-based contrast agents (GBCAs) are commonly used for enhancement in MR imaging and have long been considered safe when administered at recommended doses. However, since the report that nephrogenic systemic fibrosis is linked to the use of GBCAs in subjects with severe renal diseases, accumulating evidence has suggested that GBCAs are not cleared entirely from our bodies; some GBCAs are deposited in our tissues, including the brain. GBCA deposition in the brain is mostly linked to the specific chelate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
116
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(124 citation statements)
references
References 102 publications
(224 reference statements)
3
116
0
5
Order By: Relevance
“…Most preclinical studies also fail to acknowledge the delay between the identification of symptoms of stroke and the start of treatment, which is typically a couple of hours for most stroke patients. Also concerning the post-stroke assessment of BBB integrity as well as in other conditions where the integrity of the barrier might be compromised, gadolinium-based studies of microvascular integrity performed have shown limited sensitivity to detect low levels of extravasations across the BBB [69]. The facts discussed above highlight the urgent need to utilize technology that would better represent the disease conditions in humans.…”
Section: Strokementioning
confidence: 99%
“…Most preclinical studies also fail to acknowledge the delay between the identification of symptoms of stroke and the start of treatment, which is typically a couple of hours for most stroke patients. Also concerning the post-stroke assessment of BBB integrity as well as in other conditions where the integrity of the barrier might be compromised, gadolinium-based studies of microvascular integrity performed have shown limited sensitivity to detect low levels of extravasations across the BBB [69]. The facts discussed above highlight the urgent need to utilize technology that would better represent the disease conditions in humans.…”
Section: Strokementioning
confidence: 99%
“…Particularly, the concern emerges by the presence of gadolinium in the brain of patients that received repeated administration of chelated gadolinium contrast agents for MRI . The dechelation of free Gd(III) ions from unstable contrast agents is considered the main cause for the observed accumulation . Also, it was reported a relation between the onset of nephrogenic systemic fibrosis (NSF) and the administration of gadolinium contrast agents in patients suffering from severe renal disease .…”
Section: In Vitro and Animal Model Safety Assessmentsmentioning
confidence: 99%
“…In musculoskeletal applications, CEUS represents a complementary investigative approach, which offers certain advantages in comparison to conventionally used diagnostic instruments such as DCE-MRI or DCE-CT. 34 Contrary to MRI, CT and X-ray examinations, the costeffective CEUS can be safely used in patients with renal impairment, without ionizing radiation or deposition of contrast agents in human body and fear of claustrophobia. 15,[35][36][37] Considering, among other things, the resolution and frame rate of CEUS, whose detail accuracy is superior to conventional MRI, CEUS may soon be able to support other time-consuming and cost-intensive medical investigations for various indications. 36…”
Section: Discussionmentioning
confidence: 99%